THE EFFECTIVENESS OF UTILIZING PICTURE CARDS IN ENHANCING STUDENTS VOCABULARY SKILLS - Luruk, Fransiska Densiana; Bouk, Edmundus; Manahutu, Natalia (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2023)
The purpose of this research was to know whether using picture cards is effective to improve the students’ vocabulary achievement and to analyse the students’ difficulties in learning vocabulary using picture cards. The method used in this study was Pre-Experiment design type one-group pre-test and post-test. The population in this research were 273 students of tenth grade become the sample were 15 students of the Language Class. This study was conducted at SMAS K Warta Bakti Kefamenanu. The instrument that the researcher used was vocabulary test. The research result shows that using picture cards as media in teaching vocabulary could improve their vocabulary achievement. The research findings the frequency and rate percentage of the students’ vocabulary in pre-test from 15 students, there were no students got Excellent, Good, Fair category, 15 or 100% students classified into Very Poor category. While the frequency and rate percentage of the students’ vocabulary in post-test from 15 students, there were 4 or 26.6% students classified into Excellent, 10 or 66.6% students classified into Good, 1 or 6.6% students classified into Fair, there was no students Very Poor category. The researcher concluded that the score and rate percentage in post-test was greater than the rate percentage in pre-test. It means that the students’ vocabulary was improved after treatment by using picture card.